La Ciudadanía en las Constituciones Mexicanas del Siglo XIX: Inclusión y Exclusión Político-Social en la Democracia Mexicana - Velázquez Delgado, Graciela (Acta Universitaria, 2008)
During the nineteenth century, Mexican society was moving toward the formation of a new nation and with it, a new organization of the State. However, it is not possible to speak of the creation of citizenship without acknowledging that this was carried out under circumstances which were very unequal for the individuals concerned: those who developed this concept and framed it in the Constitution always had in mind the exclusion of a majority of the population. Under these circumstances, citizenship emerges as a category that includes not only specific policies, but also values and standards of economic, social, and cultural natures, in their broadest sense.